Barriers and facilitators in the implementation of mobilization robots in hospitals from the perspective of clinical experts and developers - Angelika Warmbein; Ivanka Rathgeber; Janesca Seif; Amrei C. Mehler-Klamt; Lena Schmidbauer; Christina Scharf; Lucas Hübner; Ines Schroeder; Johanna Biebl; Marcus Gutmann; Inge Eberl; Michael Zoller; et al. (BMC, 2023)
Abstract Background Early mobilization can help reduce severe side effects such as muscle atrophy that occur during hospitalization. However, due to time and staff shortages in intensive and critical care as well as safety risks for patients, it is often difficult to adhere to the recommended therapy time of twenty minutes twice a day. New robotic technologies might be one approach to achieve early mobilization effectively for patients and also relieve users from physical effort. Nevertheless, currently there is a lack of knowledge regarding the factors that are important for integrating of these technologies into complex treatment settings like intensive care units or rehabilitation units. Methods European experts from science, technical development and end-users of robotic systems (n = 13) were interviewed using a semi-structured interview guideline to identify barriers and facilitating factors for the integration of robotic systems into daily clinical practice. They were asked about structural, personnel and environmental factors that had an impact on integration and how they had solved challenges. A latent content analysis was performed regarding the COREQ criteria. Results We found relevant factors regarding the development, introduction, and routine of the robotic system. In this context, costs, process adjustments, a lack of exemptions, and a lack of support from the manufacturers/developers were identified as challenges. Easy handling, joint decision making between the end-users and the decision makers in the hospital, an accurate process design and the joint development of the robotic system of end-users and technical experts were found to be facilitating factors. Conclusion The integration and preparation for the integration of robotic assistance systems into the inpatient setting is a complex intervention that involves many parties. This study provides evidence for hospitals or manufacturers to simplify the planning of integrations for permanent use. Trial registration DRKS-ID: DRKS00023848; registered 10/12/2020.